2018
DOI: 10.1016/j.jsat.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for discontinuation of buprenorphine treatment for opioid use disorders in a multi-state sample of Medicaid enrollees

Abstract: Introduction: Recent U.S. trends demonstrate sharp rises in adverse opioid-related health outcomes, including opioid use disorder (OUD), overdose, and death. Yet few affected people receive treatment for OUD and a minority of those who receive treatment are effectively retained in care. The purpose of this study was to examine duration of buprenorphine treatment for OUD following treatment initiation to identify risk factors for early discontinuation. Methods: We analyzed insurance claims from the 2013–2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 49 publications
11
111
2
Order By: Relevance
“…We also excluded patients who had documented substance use disorder (SUD) or who used buprenorphine during the baseline period. We did not distinguish buprenorphine formulations approved for pain because they were infrequently used and may be used off‐label for opioid use disorder . Opioid formulations used for cough/cold were not included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…We also excluded patients who had documented substance use disorder (SUD) or who used buprenorphine during the baseline period. We did not distinguish buprenorphine formulations approved for pain because they were infrequently used and may be used off‐label for opioid use disorder . Opioid formulations used for cough/cold were not included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The State Targeted Response funding for the opioid epidemic from SAMHSA via the 21st Century Cures Act now requires states to monitor population-level receipt of MOUD and adherence to treatment. This is critical as studies have repeatedly shown that many patients who receive buprenorphine (24)(25)(26) or XR-naltrexone (27,28) only do so for 30-60 days, falling far short of a minimum threshold of 6-12 months thought to be necessary to confer sustained benefit (29,30).…”
Section: Treatment: Engagement In Carementioning
confidence: 99%
“…Further, premature treatment drop out has long plagued the field. Among the subgroup of people with OUD who initiate medication-based treatment, a great majority discontinue during the first few weeks or months (23)(24)(25)(26). Less is known about long-term recovery trajectories beyond 6 months (60).…”
Section: Current Progressmentioning
confidence: 99%
“…Induced by the healthcare system: The barriers include lack of full or proper insurance coverage (e.g., in the California Medicaid program, naloxone is covered as an FFS medication, and managed care plans like capitation do not cover the drug), high costs of medications, limited number of providers/counselors resulting in a dearth of programs or long waiting lists, a low percentage of licensed physicians having a secured waiver that is required to provide MAT or the majority of counties lacking a treatment-waivered physician, insufficient education among pharmacists (this can be resolved by educational materials through improved FDA-approved formulations), the short-term period of opioid substitution programs, and bureaucratic requirements for program entry/enrollment [ 73 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Resultsmentioning
confidence: 99%